Vikings in Scotland An Archaeological Survey - Graham-Campbell, James (Edinburgh University Press, 2022)
This book provides a full overview of the archaeology of the Vikings in Scotland, incorporating many results from the recent period of intense fieldwork and excavation. This work has necessitated a thorough re-appraisal of our knowledge of the process, nature and extent of Scandinavian settlement in Scotland. Concentrating on the Viking and Late Norse periods which span the eight to thirteenth centuries in northern and western Scotland, the chronological range allows for the Norse impact to be placed in its wider context, commencing with the native background. The scope of the book will enable Scotland, archaeologically one of the best documented areas of the Viking world, to be placed in the overall context of the period in Europe. Fully illustrated with over ninety photographs, figures and distribution maps, this book will be accessible to students and teachers of the Viking Age, and the archaeology and history of Scotland, as well as to the general reader. First survey of Viking Archaeology in over 50 years Written by two Viking experts
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jun 2022)
Keywords: Geschichte 793-1066; Scottish Studies; HISTORY / Europe / Great Britain / General; Excavations (Archaeology) -- Scotland; Northmen -- Scotland; Vikings -- Scotland; Wikinger; Ausgrabung; Funde; Siedlung; Schottland